2015
DOI: 10.1159/000440947
|View full text |Cite
|
Sign up to set email alerts
|

Early- and Middle-Term Surgical Outcomes in Patients with Heterotaxy Syndrome

Abstract: Objectives: Heterotaxy syndrome is a recognized risk factor for surgical cardiac interventions. We evaluated the early- and middle-term results of a surgical intervention for patients with heterotaxy syndrome. Methods: A total of 42 patients with heterotaxy syndrome were enrolled (September 2008 to March 2015). Left and right atrial isomerism were identified in 26% (11 out of 42) and 74% of patients (31 out of 42), respectively. The median age of the patients at the time of surgery was 6.8 months (range: 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
6
22
3
2
Order By: Relevance
“…We found a predominance of RAI opposed to LAI, as reported in the literature, 13,14,16,[20][21][22][23][24][25] with a prevalence at our institution of 58.5% versus 41.5%, respectively. We agree with be appropriately diagnosed and classified in the preoperative setting with help from the auxiliary diagnostic team at our institution.…”
Section: Resultssupporting
confidence: 83%
“…We found a predominance of RAI opposed to LAI, as reported in the literature, 13,14,16,[20][21][22][23][24][25] with a prevalence at our institution of 58.5% versus 41.5%, respectively. We agree with be appropriately diagnosed and classified in the preoperative setting with help from the auxiliary diagnostic team at our institution.…”
Section: Resultssupporting
confidence: 83%
“…HS has long been known to be a challenging disease with suboptimal short-and midterm outcomes. [4][5][6]12 Although some recent reports have suggested improved outcomes over time, [7][8][9]13,14 other studies have not found improved survival in the current era. 15,16 These discrepancies among reported outcomes in HS may, at least in part, be due to small sample sizes and short follow-up times in previous series.…”
Section: Figurementioning
confidence: 99%
“…Surgical outcomes for the Blalock-Taussig-Thomas shunt and the Glenn, Kawashima, and Fontan operations have improved over time, but overall, the prognosis for patients with heterotaxy syndrome is significantly worse than for patients with other congenital heart diseases, 5,21 possibly because the factors conferring increased mortality risk following these procedures-such as neonatal presentation requiring surgery, 22 pulmonary venous obstruction or stenosis, 10,22,23 atrioventricular valve dysfunction, [21][22][23] unplanned reoperation, 21 total anomalous pulmonary venous return, 21 extracorporeal membrane oxygenation use, 21 arrhythmia, 10 and longer duration of intensive care unit stay 10 -are more likely to be seen in patients with heterotaxy syndrome. In addition, functional asplenia in these patients carries a higher risk of sepsis, 10,17 and gastrointestinal issues can lead to poor feeding and poor weight gain.…”
Section: Discussionmentioning
confidence: 99%